Financial Performance and Banking Profitability: A Study of Banking Companies Listed on the Indonesia Stock Exchange - Selfiana Talunohi; Ike Rukmana Sari; Jernih Bestariani Waruwu; Munawarah Munawarah (SEAN Institute, 2026)
This study examines to analyze the effect of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Operating Expenses to Operating Income (BOPO), and Loan to Deposit Ratio (LDR) on profitability as measured by Return on Assets (ROA) in banking companies listed on the Indonesia Stock Exchange during the 2022–2025 period. This research uses a quantitative approach with secondary data obtained from annual financial reports. The sampling technique used purposive sampling, resulting in 35 banking companies with a total of 140 observations. The analytical methods employed include descriptive statistics, classical assumption tests, multiple linear regression analysis, hypothesis testing (t-test and F-test), and coefficient of determination (R²) using SPSS. The CAR variable has a minimum value of -0.45 and a maximum value of 7.48 with a mean of 2.9843, and shows a standard deviation of 2.85325. The NPL variable has a minimum value of -12.38 and a maximum value of 10.94 with a mean of 0.4213 and shows a standard deviation of 7.66889. The BOPO variable has a minimum value of -4.34 and a maximum value of 10.33 with a mean of 3.5687, and shows a standard deviation of 3.89921. Meanwhile, LDR has a minimum value of -0.36 and a maximum value of 9.78 with a mean of 4.0120, and shows a standard deviation of 3.39202. The ROA variable has a minimum value of -3.15 and a maximum value of 2.67 with a mean of 0.2120 and shows a standard deviation of 1.12624.In conclusion, financial performance reflected by CAR, NPL, BOPO, and LDR plays an important role in improving banking profitability. This study is expected to provide insights for bank management, investors, and future researchers.